Analisis Faktor yang Berhubungan dengan Pemberdayaan Tim Pendamping Keluarga untuk Pencegahan Stunting di Kota Binjai Tahun 2022 - Gea, Handerman Vitu; Purba, Jenny Marlindawani; Tarigan, Frida Lina (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2023)
The aim of this research is to analyze factors related to the success of empowering the Family Assistance Team (TPK) to prevent stunting in Binjai City. The approach used in this research is a mixed methods research design which is carried out in two stages of activities, namely quantitative data collection using SPSS data analysis which aims to obtain factors related to the empowerment of the Family Assistance Team and a qualitative approach which aims to obtain further explanation. further regarding the factors inhibiting and supporting the success of empowering the Family Assistance Team through interview and observation techniques. The population in this study was 114 Family Assistance Teams in South Binjai District with a sample of 53 Family Assistance Team Cadres while the research supporting informants were 10 people from Health Officers, PLKB, Village Heads and Community Figures. This research resulted in findings that the variables of communication, resources, disposition and bureaucracy have an influence on the success of empowering the Family Assistance Team in Binjai City in 2022. The inhibiting factor in this research is the communication of the Family Assistance Team to the community, where the community is still limited in receiving information regarding problems. stunting correctly, giving rise to the wrong meaning, this is because the public does not understand the problem of stunting properly and does not have materials or media for information on stunting problems. The disposition factor is also an inhibiting factor in the success of empowering the Family Assistance Team in the city of Binjai, this is because the community does not know for sure the government programs and policies in handling stunting that are currently running in their area, making it difficult for them to participate in achieving success in accelerating stunting reduction. With these findings, it is hoped that the Family Assistance Team can provide education to the community by using effective and focused communication to provide understanding to the community regarding programs and handling to accelerate stunting reduction so that the community's perception of stunting can change and the community can recognize it correctly and want to be involved in supporting it. Government program. This study produced a guidebook for the successful empowerment of the Family Assistance Team.